The formal center in literature : explorations from Poe to the present - Kopley, Richard (Studies in English and American literature and culture., 2018)
An investigation of the phenomenon of the framed formal center in literature of the last 180 years, illuminating both the works and correspondences among works of different genres, periods, and nations.